EKSPLORASI FAKTOR-FAKTOR PENGHAMBAT KEMAMPUAN KOMUNIKASI SISWA PADA METODE TANYA JAWAB PEMBELAJARAN IPA - Aini, Mellyatul; Pamungkas, Zakaria Sandy; Widoretno, Sri; Aini, Meliyana (ScienceEdu, 2024)
Students' communication skills are very important in implementing the merdeka curriculum, especially in science subjects which are relevant to students' daily lives. Merdeka curriculum in science learning directs teachers to create contextual learning contexts to develop students' abilities in explaining ideas and understanding based on facts and logical reasoning through the question and answer method. This research explores the factors inhibiting students' communication skills in the question and answer method in science learning using the merdeka curriculum. This research uses a qualitative approach with a case study type of research in class 8D of Diponegoro Islamic Junior High School Surakarta academic year 2023/2024. The data collection techniques used were observation, interviews, and questionnaires. Data analysis uses the Miles, Huberman, and Saldana analysis models: data condensation, data display, and conclusion drawing. The research results show that the factors inhibiting students' communication skills consist of understanding the material, self-confidence, interest, and motivation as well as content and learning context which are still conceptual. It is hoped that the results of the research can provide information and input for teachers to improve the quality of learning by improving the content and learning context so that students are interested and attracted to science learning.